PENGARUH PEMBERIAN PAKAN DALAM WAKTU BERBEDA TERHADAP BOBOT KARKAS DAN PERSENTASE KARKAS KAMBING KACANG JANTAN - Abdullah Naser (Universitas Tadulako, 2006)
This research was done at the eksperimental station Pengawu Sub District, South Palu District, City of Palu, Central Sulawesi Province. For 10 week from Mei 19, until August 11, 2005. this research was aimed at studying body weight and carcass percentage of male Kacang goat at different time of diet giving. Fitteen male Kacang goat aged of 10 – 12 months with 10,10 – 16,10 early body weight from local farmer around Palu City were used. The goats were in individual confinement with 15 individual size of 75 x 75 x 75 where each confinement was put food and water. Environmental design used for this research is a completely Randomized Design with coisist of treatments and 3 groups as replications. The treatments were allocated with 5 differents of eating time, i.e. WM1 (diet giving at 8 am), WM2 (diet giving at 9.30 am), WM3 (diet giving at 11 am), WM4 (diet giving at 12.30 pm) WM5 (diet giving at at 2 pm). Results showed that diet giving at different time gave very significant effect (P<0,01) on both of the parameters observed